Дослідження впливу тугоплавких часток у шлаку на адгезію до вогнетриву - Сігарьов, Є.М.; Недбайло, М.М.; Похвалітий, А.А.; Довженко, О.В. (Physico-technological Institute of Metals and Alloys, 2023)
The article theoretically and experimentally substantiates the possibility of regulating the ratio of low and high temperature phases in the final converter slag by the addition of calcium and magnesium oxides, as well as the effect of adding refractory particles of different fractions on the change in the wetting angle and the adhesion of the slag to the surface of the periclasecarbon refractory.